KAJIAN NERACA AIR KAWASAN AKIBAT PENGAMBILAN AIR BAWAH TANAH OLEH SEKTOR PERTANIAN - Effendi, Rahmat; Rizal, Nanang Saiful; Abadi, Taufan (Universitas Muhammadiyah Jember, 2017)
Water balance can be used as a guide to the presence or absence of water in an area. In the concept of the hydrological cycle that the amount of water in a certain area on the surface of the earth is influenced by the amount of water entering (input) and out (put) in a certain period. Balance input and water output somewhere known as water balance. Since water is dynamic, the water balance value changes from time to time so that somewhere there may be surplus or deficit. If the shortage and excess water is in extreme circumstances can certainly cause disasters, such as floods or drought. The disaster can be prevented or mitigated if good management of the land and the environment is carried out. The water balance is a water balance for agricultural land use in general. This balance sheet is useful in considering the suitability of agricultural land, arranging planting and harvesting schedules, arranging irrigation water supply in the right amount and time. It cannot be denied that some areas of Java and Madura have experienced water shortages, of all the water earth 97.5% is salt water, fresh water is 2.5%.This not entirely surface water and ground water. In Kabupaten Jember, especially in the area of underground water sampling (ABT) conducted by drilling wells in community development projects from the results of this study is expected to help and provide solutions to communities in the study area in the form of water buildings for storage of agricultural water reserves.Keywords:Reviewof Craft Balance